Efficacy of Ozonated Sunflower Oil on the Periodontal Status of Brazilian Air Force Recruits: A Randomized Controlled Clinical Trial - Liana Kalczuk; Sheila Cavalca Cortelli; Davi Romeiro Aquino; Fabrizia Henriques Bonates; Maria Valéria de Campos Neves; Priscila Bernardo Perrenoud; Argemiro Soares da Silva Sobrinho; José Elias Matieli (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To observe the impact of military training on the oral health of Brazilian Air Force (FAB) recruits in the first phase and to assess the efficacy of ozonated sunflower oil (Oleozon) in improving the periodontal indices of FAB recruits in the second phase. Material and Methods: In the observational phase, PPD (periodontal probing depth), CAL (clinical attachment level), PI (plaque index), GI (gingival index), and DMFT (decayed, missed, and filled teeth) values were compared before and at the end of military training. In the interventional phase, a randomized, double-anonymized, placebo-controlled study was conducted to evaluate whether the daily use of oleozon added to toothpaste would improve periodontal indices. Results: At the end of their military training, recruits exhibited a significant worsening in periodontal disease indicators, resulting in increased dental costs for FAB and increased duty absence. In the second phase, a substantial reduction in PPD and GI (p<0.004 and p<0.001) was observed in the oleozon group. Conclusion: Oleozon, in association with toothpaste brushing, was superior to brushing alone in improving the periodontal health. Despite the need for further studies, it is proposed that oleozon should be included in the oral hygiene protocol for Brazilian Air Force recruits, thereby reducing periodontal risk and dental costs.